ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA INTERAKTIF MENGENAL EMOSI PADA PELAJARAN BAHASA INDONESIA KELAS II SEKOLAH DASAR - Kartika, Syifa; Mohamad Syarif Sumantri; Engga Dalion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of this research is based on the emotional aspect in student development, particularly in recognizing various types of emotions and expressing them appropriately. Learning media can serve as a means for students to recognize and express their emotions. Therefore, the aim of this research is to analyze the needs of students and teachers for an interactive storybook as a learning medium to introduce emotions in the second-grade Indonesian Language subject at elementary school. The method used in this research is Research and Development (R&D), with focusing on the first stage of the ADDIE model, which is the need analysis stage. The research subjects consisted of 61 second-grade students (classes 2A and 2B) and two teachers at SDN Rawamangun 02. Data collection techniques consist of student needs questionnaires and teacher interviews, followed by data processing and analysis using the Responden Achievement Level formula and descriptive analysis. The result showed that 82% of students need a fun interactive storybook to help them recognize emotions during Indonesian Language learning. Teacher interviews also indicated a need for more varied media that are tailored to student conditions, especially for students with special needs. The conclusion of this research is the product to be developed will be designed by considering visual aspect, interactivity, and simplified language to match the developmental stage of second-grade elementary school students.